Cultural heritage care and management theory and practice - Salvatore, Cecilia Lizama 1958- (Rowman & Littlefield, 2018)
"Cultural Heritage Care and Management: Theory and Practice considers all the different components of cultural heritage and provides the tools, technology, and methodology for organizing and arranging, cataloging and describing, exhibiting, providing access, and preserving and conserving these elements"-- Provided by publisher.